The impact of comorbidities on productivity loss in asthma patients. Issue 1 (December 2016) - Ehteshami-Afshar, Solmaz; FitzGerald, J.; Carlsten, Christopher; Tavakoli, Hamid; Rousseau, Roxanne; Tan, Wan; Rolf, J.; Sadatsafavi, Mohsen
Abstract Background Health-related productivity loss is an important, yet overlooked, component of the economic burden of disease in asthma patients of a working age. We aimed at evaluating the effect of comorbidities on productivity loss among adult asthma patients. Methods In a random sample of employed adults with asthma, we measured comorbidities using a validated self-administered comorbidity questionnaire (SCQ), as well as productivity loss, including absenteeism and presenteeism, using validated instruments. Productivity loss was measured in 2010 Canadian dollars (). We used a two-part regression model to estimate the adjusted difference of productivity loss across levels of comorbidity, controlling for potential confounding variables. Results 284 adults with the mean age of 47.8 (SD 11.8) were included (68 % women). The mean SCQ score was 2.47 (SD 2.97, range 0–15) and the average productivity loss was 317.5 per week (SD 858.8). One-unit increase in the SCQ score was associated with 14 % (95 % CI 1.02–1.28) increase in the odds of reporting productivity loss, and 9.0 % (95 % CI 1.01–1.18) increase in productivity loss among those reported any loss of productivity. A person with a SCQ score of 15 had almost 1000 per week more productivity loss than a patient with a SCQ of zero. Conclusions Our study deepens the evidence-base on the burden of asthma, by demonstrating that comorbidities substantially decrease productivity in working asthma patients. Asthma management strategies must be cognizant of the role of comorbidities to properly incorporate the effect of comorbidity and productivity loss in estimating the benefit of disease management strategies.